Exocrine Pancreatic Carcinoma with Hypoglycemia in a Dog - Roberto, Gabriela Basilio; Magro, Ane Louise; Seki, Meire Christina; Tranquilim, Marcos Vinicius; Ziliotto, Liane (Acta Scientiae Veterinariae, 2016)
Background: Primary pancreas neoplasms are rare, representing less than 0.5% of all veterinary tumors. They are highly aggressive, and most of the patients have unspecifc clinical signs until diagnosis. Although the treatment of choice is surgical resection, only 15 to 20% of the patients may undergo surgery and be cured. Survival is variable after diagnosis, ranging from 4 to 10 months. Prognosis is poor due to the aggressiveness and advanced stage of the disease at the moment of diagnosis, and the weak response to all existing treatments. The objective of this study was to report a case of exocrine pancreatic carcinoma in a dog with hypoglycemia. Case: The present study describes a clinical case of exocrine pancreatic carcinoma in the Clínica Escola de Veterinária (CEVET) at UNICENTRO-PR. The patient was taken to the CEVET and the main complaint of the owner was a volume increase in the ventral thoracic region. During the physical examination, it was observed that this increased volume was a mammary tumor in the third gland of the right side of the body. The animal showed no other symptoms and the diagnosis of exocrine pancreatic cancer was only possible because glucose levels in routine examination were below the normal reference value for the species (47 mg/dL). After the glycemic curve was determined, it was observed that glucose levels were below reference values, even after feeding (at 8 am and 7 pm). Suspicion of a metastasis of mammary tumor in the pancreas, or even a pancreatic tumor, was then raised. Blood insulin was performed and a 42.3 µUI/mL increase was observed. Insulin reference values range from 5 to 20 µUI/mL. Based on these results, and after the owner signed an informed consent form, exploratory celiotomy was carried out in order to assess pancreatic changes and, if possible, to excise any nodule that was found. However, instead of a single nodule, as expected, diffuse lesions with several whitish micronodules that showed frm consistency were observed. As it was not possible to excise all the nodules, the option was to carry out pancreas biopsy and mastectomy. Discussion: The absence of characteristic clinical signs or radiological changes suggestive of a tumor in this clinical case is supported by data in the literature as, most of the times, conclusive diagnosis is carried by histopathological analysis of the structure resected in the surgery. The pancreas is made up of ductal, acinar, and endocrine/neuroendocrine cells supported by conjunctive and endothelial tissue and lymphocytes. Malignant neoplasms may originate from any of these types of cells. However, the literature describes that most human and animal patients with pancreatic tumors present late and unspecifc clinical signs, whereas in this report the animal did not show any clinical signs. The treatment of choice is surgical resection, and total or partial pancreatectomy or pancreatoduodenectomy have been used in humans and dogs. Because of that, support therapy is highly important for improved quality of life. In this case, the presence of hypoglycemia, different from most reports, which describe hyperglycemia, led to further laboratory analysis. The presence of hyperinsulinemia and, later on, the fndings of the pancreas biopsy, led to the diagnosis of exocrine pancreatic cancer. It was concluded that this type of tumor needs to be further analyzed and studied in dogs, as case reports such as this one are not common in veterinary. Keywords: neoplasia, celiotomy, hyperinsulinemia.